Stakeholder mapping Report: Partnerships and programs on opportunity crops across Africa - Otieno, Gloria; Grazioli, Francesca; Mendonce, Sharon; Acasto, Filippo; Elbilali, Hamid; Rokka, Susanna; Saarikko, Janne; Diadie, Halima; Maarouhi M, Inoussa; Baboussouna, Awal; Dambo, Lawali; Tietiambou, Fanta; et al. (2025)
Neglected and underutilized species (NUS)—often called opportunity crops—are increasingly recognized as vital for Africa’s food systems. They contribute to climate resilience, improved nutrition, diversified livelihoods, and biodiversity conservation. Yet, despite their potential, these crops remain underrepresented in agricultural policies, markets, and research agendas.